The puzzle of chloroplast vesicle transport – involvement of GTPases - Karim, Sazzad; Aronsson, Henrik (Frontiers in Plant Science, 2014)
In the cytosol of plant cells vesicle transport occurs via secretory pathways among the endoplasmic reticulum (ER) network, Golgi bodies, secretory granules, endosome and plasma membrane. Three systems transfer lipids, proteins and other important molecules through aqueous spaces to membrane-enclosed compartments, via vesicles that bud from donor membranes, being coated and uncoated before tethered and fused with acceptor membranes. In addition, molecular, biochemical and ultrastructural evidence indicates presence of a vesicle transport system in chloroplasts. Little is known about the protein components of this system. However, as chloroplasts harbour the photosynthetic apparatus that ultimately supports most organisms on the planet, close attention to their pathways is warranted. This may also reveal novel diversification and/or distinct solutions to the problems posed by the targeted intra-cellular trafficking of important molecules. To date two homologues to well-known yeast cytosolic vesicle transport proteins, CPSAR1 and CPRabA5e, have been shown to have roles in chloroplast vesicle transport, both being GTPases. Bioinformatic data indicate that several homologues of cytosolic vesicle transport system components are putatively chloroplast-localized and in addition other proteins have been implicated to participate in chloroplast vesicle transport, including vesicle-inducing protein in plastids 1 (VIPP1), thylakoid formation 1 (THF1), snowy cotyledon 2/cotyledon chloroplast biogenesis factor (SCO2/CYO1), curvature thylakoid 1 (CURT1) proteins, and a dynamin like GTPase FZO-like (FZL) protein. Several putative potential cargo proteins have also been identified, including building blocks of the photosynthetic apparatus. Here we discuss details of the largely unknown putative chloroplast vesicle transport system, focusing on GTPase-related components.